Discovering Antioxidant Molecules in the Archaea Domain: Peroxiredoxin Bcp1 from Sulfolobus solfataricus Protects H9c2 Cardiomyoblasts from Oxidative Stress. (26th September 2016) - Sarcinelli, Carmen; Fiorentino, Gabriella; Pizzo, Elio; Bartolucci, Simonetta; Limauro, Danila
Abstract : Peroxiredoxins (Prxs) are ubiquitous thiol peroxidases that are involved in the reduction of peroxides. It has been reported that prokaryotic Prxs generally show greater structural robustness than their eukaryotic counterparts, making them less prone to inactivation by overoxidation. This difference has inspired the search for new antioxidants from prokaryotic sources that can be used as possible therapeutic biodrugs. Bacterioferritin comigratory proteins (Bcps) of the hyperthermophilic archaeon Sulfolobus solfataricus that belong to the Prx family have recently been characterized. One of these proteins, Bcp1, was chosen to determine its antioxidant effects in H9c2 rat cardiomyoblast cells. Bcp1 activity was measured in vitro under physiological temperature and pH conditions that are typical of mammalian cells; the yeast thioredoxin reductase ( y TrxR)/thioredoxin ( y Trx) reducing system was used to evaluate enzyme activity. A TAT-Bcp1 fusion protein was constructed to allow its internalization and verify the effect of Bcp1 on H9c2 rat cardiomyoblasts subjected to oxidative stress. The results reveal that TAT-Bcp1 is not cytotoxic and inhibits H2 O2 -induced apoptosis in H9c2 cells by reducing the H2 O2 content inside these cells.